(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2023)
Based on many past studies regarding Social Media Applications (SMAs) rarely focus on aspects of continuous use and Perceived Privacy (PP). The increasing user awareness issue regarding PP in using SMA is escalating due to various cybersecurity threats, such as malware, software, password and Man-in-the-Middle (MitM) attacks. Accordingly, this study examines the effect of users’ PP on System Quality (SQ), Information Quality (IQ), Service Quality (SVQ), User Satisfaction (US) and Usage (USG) based on the DeLone and McLean Information System (IS) Success Model. A total of 345 samples were used for this study using the convenience sampling approach and SmartPLS 3 as the analysis tool. Based on the study’s results, it was discovered that SVQ and IQ affect the use of SMA. In addition, it was discovered that PP affects the relationship between SQ, SVQ and the use of SMA. The analysis results related to PP reveal that it is a dominant construct in the study model. Note that the importance of PP should be a solid foundation for developing an SMA application. The PP component in this study can be used as a guide and checklist for software developers to improve security features and SVQ, which is a catalyst for US and ensure that an SMA application is used continuously.